Analisis Faktor Risiko Dermatitis Kontak Pada Nelayan Rumput Laut Di Kecamatan Ponrang Kabupaten Luwu - Nurfasira, Nurfasira; Usman, Usman; Anggraeny, Rini; Thasim, Sukmawati; Hengki, Henny Kumaladewi (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Dermatitis in seaweed fishermen is a health problem often caused by direct exposure to seawater, chemicals, and sub-ideal working conditions. This study aims to analyze the risk factors for contact dermatitis in seaweed fishermen in Ponrang District, Luwu Regency. This study used a quantitative research method with a cross-sectional design. The sample consisted of 86 seaweed fishermen from Mario, Tirowali, and Muladimeng villages, selected using a proportional random sampling technique. Data were collected through questionnaires and analyzed using the Chi-square test. The results showed that most respondents (61.8%) had experienced contact dermatitis. There was a significant relationship between the duration of seawater exposure (p0.003), the use of PPE (p0.000), and personal hygiene (p=0.013) with the incidence of contact dermatitis. However, the cleanliness of the work environment did not show a significant relationship (p=0.265). It can be concluded that the duration of seawater exposure of 8 hours, inconsistent use of PPE, and poor personal hygiene are significant risk factors for the incidence of contact dermatitis.